Poder compensatório e política de defesa da concorrência: referencial geral e aplicação ao mercado de saúde suplementar brasileiro - Almeida, Sílvia Fagá de (2009)
The countervailing power created by those damaged in an asymmetrical power relationship may be beneficial in terms of welfare. The analysis based on the framework proposed by Dobson et al. (1998) drove to the conclusion that such conditions are restrictive and are directly related to the interdependence recognition and cooperation among stakeholders. It was also observed that, differently from the outcomes of Dobson et al. (1998) analysis, the creation of countervailing power may have a positive welfare effect even though parties do not recognize their interdependency and do not cooperate with each other – what depends on the relationship of price-elasticity of demand and supply. Despite the possibility of positive effects, the antitrust doctrine in Brazil and in other jurisdictions such as USA and European Community apply the countervailing power concept mistakenly or completely ignore its existence. However, the goal of antitrust policy and the creation of compensatory power are aligned: the balance of power asymmetries in relations between agents, preventing the abuse of power in the transaction. Thus, there is an incongruity between court decisions and economic theory. The conflict in applying the countervailing power concept by antitrust doctrine can be clearly observed in the Brazilian health care sector. Physicians often coordinate themselves into cooperatives in order to counteract the exercise of buying power by health insurance firms. However, this agreement among physicians, presumably competitors, has been condemned by antitrust authorities based on the interpretation that such collective bargain is a cartel – an antitrust offence. This study investigates – using panel data econometric method – if collective bargain enables physicians to exercise countervailing power and increases social welfare. The empiric analysis corroborates theoretical propositions: in the healthcare sector, at least in the price dimension, there is a possibility of positive effects related to countervailing power. However, it must be noted that such a result would be related to cooperatives condemned by CADE, which should represent the group of associations that would effectively deter economic power to counterbalance the power asymmetry in negotiations with healthcare service providers. Given that fact, it is important to reassess CADE’s decisions regarding physicians’ cooperatives as a public policy aiming to increase social welfare.